IMPLEMENTATION OF WASTE MANAGEMENT POLICY IN LAPADDE SUB-DISTRICT, UJUNG DISTRICT, AT THE PAREPARE CITY ENVIRONMENTAL AGENCY (DLH) - Rosdiana; Harman (Meraja journal, 2022)
[Full Paper] to pdf Copyright (c) 2022 Meraja journal